BOVINE SEMEN THAWED AT 28ºC OR 37ºC CAN BE USED FOR AI TILL 90 MIN POST-THAW - PAWSHE, M; BIBIN BECHA, B; UNNIKRISHNAN, MP; HARSHAN, HM; ARAVINDA GHOSH, KN (The Indian Journal of Animal Reproduction, 2022)
The post-thaw keeping quality of frozen bull semen at 15 min interval upto 150 min post-thaw was assessed following thawing under tap water (28ºC) or ideal (37ºC) temperature. Under both thawing temperatures, upto 120 min post-thaw, the progressive motility (>50%), sperm viability (>60%), sperm abnormalities (<7%) and acrosome integrity (>75%) were within the acceptable limlits of frozen bovine semen production, whereas, >40% HOSTpositive sperms were maintained upto 90 min post-thaw. Between groups, there was no difference (p>0.05) in the post-thaw outcome of seminal parameters. Thus, based upon the results of seminal parameters of frozen thawed bull semen, it can be suggested that semen straws thawed under tap water (28ºC) or ideal (37ºC) temperature can be used for artificial insemination till 90 min post-thaw in situations where carrying of liquid nitrogen cylinder is not possible.